2022
DOI: 10.1186/s40594-022-00335-1
|View full text |Cite|
|
Sign up to set email alerts
|

I will teach you here or there, I will try to teach you anywhere: perceived supports and barriers for emergency remote teaching during the COVID-19 pandemic

Abstract: Background Due to the COVID-19 pandemic, many universities moved to emergency remote teaching (ERT). This allowed institutions to continue their instruction despite not being in person. However, ERT is not without consequences. For example, students may have inadequate technological supports, such as reliable internet and computers. Students may also have poor learning environments at home and may need to find added employment to support their families. In addition, there are consequences to fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 62 publications
0
39
0
1
Order By: Relevance
“…In the online classroom, students are represented as avatars, text on a screen, and sound bites, potentially leading to students becoming disembodied entities and a weakened of community (30). One student wrote that she "felt cut off and sort of isolated from the class, " while another noted the "impersonalness of lectures" and the "difficulty of following lectures when the pace is not as connected with the students' ability to keep up" (18). While several instructors we interviewed noted the importance of community during ERT, two challenges stand out.…”
Section: Communitymentioning
confidence: 98%
See 1 more Smart Citation
“…In the online classroom, students are represented as avatars, text on a screen, and sound bites, potentially leading to students becoming disembodied entities and a weakened of community (30). One student wrote that she "felt cut off and sort of isolated from the class, " while another noted the "impersonalness of lectures" and the "difficulty of following lectures when the pace is not as connected with the students' ability to keep up" (18). While several instructors we interviewed noted the importance of community during ERT, two challenges stand out.…”
Section: Communitymentioning
confidence: 98%
“…As part of a research study, we conducted instructor and student surveys and interviews to identify supports and barriers during the transition to ERT (18). We found that course attributes, community, and classroom technology were the most frequent support categories that emerged from the student data and that these ideas mentioned were related to reducing cognitive load and increasing student engagement.…”
Section: Lessons Learned During Ertmentioning
confidence: 99%
“…A study conducted at the University of California, Merced (Donham, Barron, & Alkhouri, 2022) identified supports and barriers that affected both instructors and students they experienced during the emergency remote teaching. The students who participated in the study determined that 1) Tools and support for class content; 2) Mental/emotional support, and 3) Preexisting support were the most challenging in their learning.…”
Section: Mental Strugglesmentioning
confidence: 99%
“…Following publication of the original article (Donham et al, 2022 ), the authors identified an error: The wrong affiliation was listed for Jourjina Subih Alkhouri Incorrect affiliation: Department of Genetics, University of Georgia, Athens, GA, USA. Correct affiliation: Quantitative and Systems Biology Program, University of California, Merced, CA, USA.…”
Section: Correction To: International Journal Of Stem Education (2022...mentioning
confidence: 99%